Effect of nano-silica dispersed at different temperatures on the properties of cement-based materials. (1st April 2022) - Liu, Haibao; Li, Qiuyi; Ni, Songyuan; Wang, Liang; Yue, Gongbing; Guo, Yuanxin
Abstract: The influence of nano-silica (NS) on the performance of cement is largely dependent on the degree of dispersion. This study aims to clarify the influence of NS at different dispersion temperatures on the properties, such as the hydration and hardening, of cement. The optimum dispersion temperature of NS was determined by measuring the particle-size distribution, hydration heat, and mechanical strength. The microstructure and morphology of cement pastes and the content of hydration products were studied to evaluate the effect of NS at different dispersion temperatures on the properties of cement. The results indicated that the higher the temperature of NS dispersion, the smaller the particles of NS aggregations. However, the higher temperature made NS agglomerate more easily in the cement paste. The average particle size of NS in the extractive solution of cement was the smallest, and the increase in hydration degree showed that the improvement in NS on the properties of cement was greatest when the dispersion temperature was 10 °C. The 3d- and 28d-compressive strengths of the cement paste were increased by 22% and 25%, respectively. Highlights: The energy distribution of ultrasonic dispersion was studied. Higher dispersion temperature can get NS particles smaller but easier to agglomerate in cement solution. Low temperature dispersion of nano-silica is beneficial to improve the properties of cement-based materials.